EFFECTIVENESS OF THE QUESTION IMAGE CIRCLE LEARNING MODEL IN IMPROVING THE DEVELOPMENT OF CRITICAL THINKING OF MA ISLAMIYAH BALEN STUDENTS OF CLASS X: EFEKTIFITAS MODEL PEMBELAJARAN QUESTION IMAGE CIRCLE DALAM PENINGKATAN PENGEMBANGAN BERFIKIR KRITIS SISWA MA ISLAMIYAH BALEN KELAS X - Mar Atullatipah; Sely Ayu Lestari; Ernia Duwi Saputri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study was used to see the effectiveness of the Question Image Circle learning model in improving critical thinking in students of MA Islamiyah Balen. This study uses a quantitative approach with a quasi-experimental method using a pretest-posttest control group design, for data collection this study used observations of collecting pretest-posttest values ​​and questionnaires to see the effectiveness of the learning model, in this study researchers with a population of 42 children from class X consisting of 2 classes, namely the experimental class and the control class with a sample of 21 and a sample of 21 students, this study uses data analysis techniques for normality tests and Levene statistical tests to test post-test and pre-test questions while for validity and reliability tests to calculate the effectiveness of the learning model with a total of 10 questions that are valid and reliable> 0.60, namely 0.815. In the normality test and Levene statistical test, the data obtained got a value of 0.269, which means > 0.05 from the data obtained, it can be concluded that the image circle learning model in developing critical thinking is very feasible and effective for conducting research.